Pengaruh Persepsi Harga, Kualitas Pelayanan Dan Kualitas Produk Terhadap Kepuasan Konsumen Di Hotel D’prima Mega Kuningan - Salvator, Rafael; Indra Vitaharsa, Leonardo (Rifa'Institute, 2023)
Research conducted at Hotel D'prima Mega Kuningan aims to determine the effect of perceived price, service quality, and product quality on customer satisfaction. Survey respondents in this study were customers of Hotel D'prima Mega Kuningan. The sampling method used was purposive sampling. The validity and reliability of 30 respondents were tested using a total of 100 respondents in this study. The technique used is a quantitative technique with the application of SPSS 25. Based on the findings of this study, it can be concluded that customer satisfaction is influenced by three main factors: price perception, product quality, and service quality. However, service quality is not proven to have a significant effect on customer satisfaction. These variables are able to explain 46% of the variation in consumer satisfaction.